2019
DOI: 10.1002/icd.2168
|View full text |Cite
|
Sign up to set email alerts
|

Touch and look: The role of visual‐haptic cues for categorical learning in primary school children

Abstract: Benefits of synchronous presentation of multisensory compared to unisensory cues are well established. However, the generality of such findings to children's learning with visual and haptic sensory cue pairings is unclear. Children aged 6 to 10 years (N = 180) participated in a novel tabletop category‐learning paradigm with visual, haptic, or visuohaptic informative cues. The results indicated that combinations of complimentary visual and haptic cues facilitated learning above unisensory visual cues only in 8‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…A subsequent investigation into visuohaptic interactions on novel object categorization performance in children aged 6-10 years also revealed a multisensory benefit to categorization performance, but this emerged late, i.e. in 8-to 9-year-olds [179], consistent with findings on perception. Taken together with results of other studies [180,181], maturation trends were observed across all category learning conditions, suggesting that improved sensory and perceptual precision with development likely underpins multisensory integration for categorization.…”
Section: How Do Developmental Processes Across the Lifespan Affect Mu...supporting
confidence: 58%
“…A subsequent investigation into visuohaptic interactions on novel object categorization performance in children aged 6-10 years also revealed a multisensory benefit to categorization performance, but this emerged late, i.e. in 8-to 9-year-olds [179], consistent with findings on perception. Taken together with results of other studies [180,181], maturation trends were observed across all category learning conditions, suggesting that improved sensory and perceptual precision with development likely underpins multisensory integration for categorization.…”
Section: How Do Developmental Processes Across the Lifespan Affect Mu...supporting
confidence: 58%
“…These cues were behaviour cues, choice boards, communication cues, environmental cues, labels and visual directions. Regarding haptic cues, visuo-haptic cues are increasingly being used in primary school classrooms and have been found to facilitate learning (Broadbent et al. , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…, 2020). Interestingly, haptic information dominates children’s category learning over visual information especially in younger children (Broadbent et al. , 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to age eight, children's perception of size is dominated by the sense of touch. Beginning from age eight, it is helpful to integrate both visual and tactile information as this enhances spatial and perceptual judgments (Broadbent et al, 2020). By age twelve, tactile information once again dominates children's perception, and their exploration through touch becomes more accurate and nuanced by patterns (Mjsceo et al, 1999).…”
Section: Preparation For Playing An Instrumentmentioning
confidence: 99%